Case Report: Successful pregnancy after fertility-sparing surgery for ovarian clear cell carcinoma - Wang, Shubo; Li, Qian; Zhou, Bingxiu; Zhou, Fuxin (Frontiers in Oncology, 2026)
Ovarian clear cell carcinoma (OCCC) is a rare histologic subtype of epithelial ovarian cancer, often associated with chemoresistance and poor prognosis. Fertility preservation in patients with OCCC remains controversial because of its aggressive biological behavior and limited evidence supporting conservative management. We report a case of a 33-year-old woman with stage IA OCCC who underwent fertility-sparing staging surgery followed by six cycles of adjuvant chemotherapy with liposomal paclitaxel and carboplatin. Gonadotropin-releasing hormone agonist was administered concurrently to protect ovarian function. The follow-up duration was 36 months, during which the patient remained disease-free and achieved a successful full-term pregnancy after in vitro fertilization and embryo transfer. The pregnancy resulted in a full-term delivery, and the patient gave birth by cesarean section without complications. This case demonstrates that fertility-sparing surgery combined with adjuvant chemotherapy may be a feasible treatment option in carefully selected young patients with early-stage OCCC. Individualized management, comprehensive counseling, and close surveillance are essential to ensure both oncologic safety and favorable reproductive outcomes.